The heart of community engagement : practitioner stories from across the globe - Wilson, Patricia Ann (New York, NY : Routledge, 2019)
Drawing on first-hand accounts of action research in the Americas, Africa, and Asia, The Heart of Community Engagement illustrates the transformative learning journeys of exemplary catalysts for community-based change. Practitioners' stories of community engagement for social justice in the Global South elucidate the moments of insight and transformation that deepened their practice: how to deal with uncertainty, recognize their own blind spots, become aware of what is emergent and possible in the moment, and weave an inclusive bond of love, respect, and purpose. Each successive narrative adds a deeper level of understanding of the inner practice of community engagement. The stories illuminate the reflective, or inner, practice of the outside change agent, whether a planner, designer, participatory action researcher, or community development practitioner. From a shantytown in South Africa, to a rural community in India, or an informal settlement in peri-urban Mexico, the stories focus attention on the greatest leverage point for change that we, as engaged practitioners, have: our own self-awareness. By the end of the book, the practitioners are not only aware of their own conditioned beliefs and assumptions, but have opened their minds and hearts to the complex and dynamic patterns of emergent change that is possible. This book serves as a much-needed reader of practice stories to help instructors and students find the words, concepts, and examples to talk about their own subjective experience of community engagement practice. The book applies some of the leading-edge concepts from organizational development and leadership studies to the fields of planning, design, and community engagement practice. Key concepts include the deep dive of sensing the social field, seeing the whole, and presencing the emergent future. The book also provides a creative bridge between participatory action research and design thinking: user-based design, rapid prototyping, and learning from doing.
OCLC-licensed vendor bibliographic record.
Keywords: Community development; Community leadership; SOCIAL SCIENCE / Sociology / Urban; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning